Inner-city socio-spatial inclusion as a source for social development - Lebedeva, Еlena V.; Pinchuk, Igor V. (Journal of the Belarusian State University. Sociology, 2023)
Locally-specific factors in the organisation of the urban environment affect not only the physical space of the city, but also the totality of social practices and relations formed in it. Reproduction of this inner structure causes the development of the urban habitus as the exact pattern of solidarity, which consist of the unique physical, social and institutional integration mechanisms. Urban habitus is represented by the number of the qualitatively different processes of integration: making an environment of confidence, the development of peer support and the formation of the acting subject. The empirical measurement of urban habitus is based on the peculiarities of citizens’ interaction with each other.
Keywords: social development; urban environment; spatial social inclusion; habitus; social trust